Grip strength exercises for fighters (2019)
Grip strength is often overlooked and is a common weak link for many fighters. The following video showcases a few grip strength exercises for fighters. There are many other exercises to choose from, but these four have been very helpful for the fighters that I train. These exercises will tax your hands, fingers, wrist and forearms in a variety of ways.